(untitled) (Nigerian Journal of Physiological Sciences, 2025)
Kola and kola-containing beverages are among the most consumed products globally for their stimulatory and energy-boosting potentials. The precise impact of kola nut consumption on various biological indices of consumers remains debatable, necessitated by the fact that the phytochemical compositions of kola nuts are dependent on a range of factors. This study investigated the impacts of a 28-day administration of a methanolic extract of C. acuminata on the body weight and serum cholesterol indices of adult male albino rats (Wistar strain). The quantitative photochemical compositions and lethal dose (LD50) of the extract were determined using standard bioassay procedures. Rats were randomized into four experimental groups that received various concentrations of the extract: 0, 100, 150, and 200 mg/kg. Results show an LD50 of 3101.37 mg/kg for the extract, whereas flavonoids and tannins were the most abundant phytochemicals. In addition, extract administration caused a dose-dependent reduction in body weight, while significant elevations in total serum cholesterol levels were recorded in rats that received 100 and 150 mg/kg of the extract. These suggest that kola nut consumption may negatively impact on body weight and cholesterol metabolism.